PETA KEMAMPUAN PENERIMAAN PAJAK NEGARA DI PROVINSI MALUKU - Maxmilian E. Mauwa; Elisabeth Riupassa (Gapenas Publisher, 2023)
Tax plays a very important role in a state's life, especially in development because it is the largest state revenue source. State taxes collected by the Central Government are used to finance state expenditures. The plan and realization of state tax revenue in Maluku Province during 2018 - 2022 shows that almost all state tax revenue realization cannot achieve what was planned every year except 2022 that reaches the state tax revenue target. This study aimed to provide an overview of the State Tax Revenue map in Maluku Province. Quantitative data obtained were in the form of State Tax Revenue Realization Plans in Maluku Province during 2018-2022 and were obtained from the Central Bureau of Statistics for Maluku Province. The data were then analysed using Klassen Typology analysis. The study results show that income tax, Value-Added tax (VAT), and Sales Tax on Luxury Goods (STLGs) are in the leading (prime) sector, a sector with high growth and with the most dominant contribution to state tax revenues. Property taxes as well as Land and Building Rights Acquisition Fees are in developing sector, a sector that is experiencing an increase, which is indicated by high growth but still potentially low. The underdeveloped sector, namely other taxes, is a type of state tax with slow growth and a small contribution to low state tax revenues